Paleolimnology of the Santa Clara Arriba paleolake (Triassic Cuyana rift basin): integrating sedimentology and palynology - Benavente, Cecilia Andrea (2018)
The Triassic Cuyana rift basin of west-central Argentina is composed of several asymmetric half-grabens with sedimentary fill representing diverse fluvial-lacustrine systems from the syn-rift to post-rift phases of the basin. The Santa Clara Arriba Formation (SCAF) consists of Triassic continental deposits cropping out at Santa Clara Creek which represents deposits of the Santa Clara subbasin located in the middle area of the rift basin. Integrated sedimentology and palynology studies of the SCAF have recognized a deltaic-lacustrine system where low delta plain and prodelta-lacustrine facies associations characterize the depositional setting during the final stage of rifting. Sedimentologic features of the sandstone bodies entering the lake suggest a low-gradient deltaic system. The organic matter (OM) rich lacustrine facies and its palynofacies support a stratified lake interpretation. The sedimentology and palynology suggest that the SCAF paleolake was a shallow overfilled lake. Palynostratigraphic analysis constrained a late Triassic (Carnian-early Norian) age for the SCAF, providing for the first time a framework for the last infill of the Santa Clara subbasin of the Cuyana rift basin.